Digitalization Opportunities for Tourism Micro-Entrepreneurship in South Africa : An Academic Gaze - Siyanda Sifolo, Portia Pearl; Sokhela, Philasande (Indian Journal of Finance, 2022)
Framed within the technology determinism and diffusion of innovation (DOI) theory, the study aimed to evaluate digitalization opportunities that could be explored by the tourism micro-entrepreneurs (TMEs) in South Africa. A question raised in this paper is how tourism micro-entrepreneurs can improve firms’ performance through digitalization, particularly in the South African context as a developing country. A systematic review of the literature on the digitalization of micro-entrepreneurs in an African context was conducted. The study reviewed 50 publications in peer-reviewed journals between 2017 and 2021. The literature analysis revealed that there is value in the digitalization of tourism micro-entrepreneurs. However, digitalization opportunities can only be realized through coordination and collaboration with relevant stakeholders. The findings revealed that developing a digital strategy could address the change in customers’ needs, the future of work, and the preservation of historical and cultural practices while investing in tourism intelligence and improving policy regulations. The paper contributed toward adding to the limited academic gaze on tourism micro-entrepreneurship in Africa by identifying strategic prospects in digitalization.